Frequency of metabolic syndrome in schizophrenic patients (Research, Society and Development, 2021)
Introduction: Metabolic Syndrome (MS) is characterized by a set of factors that increase the risk of cardiovascular diseases related to central obesity and insulin resistance. The numbers of morbidity and mortality and socioeconomic costs to public health services are alarming and their prevalence varies according to the diagnostic criteria and the population studied. The world population has a prevalence of 25%, considering schizophrenic patients, the mean MS prevalence rate found is 32.5%. Schizophrenia is a chronic psychosis without a defined cause, a multifactorial disease that appears slowly or suddenly and is related to health problems, such as difficulty with self-care, thought processing, interpersonal relationships, which favors social isolation and difficulty in the rehabilitation process. Objectives: To determine the prevalence of metabolic syndrome (MS) in schizophrenic patients according to the international diagnostic criteria of NCEP / ATP / III and IDF. Methods: Cross-sectional and analytical epidemiological study. Socioeconomic, anthropometric, clinical and biochemical data were collected. For data analysis, ​​absolute, relative and multivariate frequency measures were used, and a significance level of 5% was considered. Results: The frequency of MS was 38.9 and 43.1%, NCEP / ATP / III and IDF respectively. Women had a greater presence of MS and altered waist circumference than men. The group with MS changed more frequently in terms of individual components changed compared to the group without MS. Conclusion: The frequency of MS and its individual components altered was high, especially among women.